Detection of Human Cytomegalovirus (HCMV) among Infertile Male in AL-Najaf governorate. - Kareem Thamir Mashkoor; Ghanim Aboud Al-Mola; Saif Jabbar Yasir (Kufa Journal for Nursing Sciences)
The current study aimed to detect human cytomegalovirus among infertile individual. Blood and seminal fluid collected of 300 infertile male randomly, ELISA technique was used to know the activity of humoral immunity among them through measuring anti-HCMV IgM and IgG antibodies, the result revealed that 31 (11%) were positive for IgM result and 234 (78%) were positive for IgG. The PCR technique showed that out of 300 samples only 22 (7.4%) gave positive results, In case of control group, results were negative for anti- HCMV IgM antibodies in ELISA test and PCR technique. While IgG gave a weak positive results.